Information Systems Management – Understanding Modular Approach - Seppo Sirkemaa (Engineering and Technology Publishing, 2025)
Information systems management in an ongoing process. There is a need to map and evaluate technological innovations and evaluate whether they should be adapted to the organization. Technologies are continuously changing, but development should be a managed process so that changes follow architectural guidelines, and eventually add value to business operations and activities. In this article we approach information systems management with a modular approach. Here it refers to a situation where the system is combination of models that are integrated together. These modules have different functions but should work together as smoothly as possible. Clearly, this is a challenge for developers of information systems.